The efficacy and safety of endoscopy-assisted anterior cervical discectomy and fusion for the treatment of cervical spondylotic myelopathy - Wei, Jingchao; Gao, Shangju; Li, Xiaohua; Guo, Yusong; Meng, Yuxin; Li, Wenyi (Frontiers in Surgery, 2026)
ObjectiveThe aim of this study was to describe the surgical technique of endoscopy-assisted anterior cervical discectomy and fusion (ACDF), to evaluate the advantages, efficacy, and safety of this procedure for the treatment of cervical spondylotic myelopathy (CSM).MethodsThe clinical data of patients with CSM treated with endoscopy-assisted ACDF from January 2023 to December 2023 were retrospectively reviewed. And 35 patients, including 13 females and 22 males, were included in this study. Endoscopic assisted ACDF surgery was described step by step in detail, and clinical and imageological assessment were performed before and after operation and follow-up.ResultsAll 35 patients underwent endoscopy-assisted ACDF surgery successfully, and were followed up for 12.9 ± 2.1 months (range 9∼18 months). The operation time was 74.4 ± 10.7 min (range 60∼100 min). Postoperative drainage volume was 14.1 ± 5.8 mL (range 5∼25 mL). No complications were observed. There were no complications, aggravation of neurological symptoms after operation, and the JOA score at the last follow-up was significantly improved compared with that before operation (15.7 ± 0.8 vs. 10.3 ± 1.9, P < 0.001). At the last follow-up, the C2-C7 Cobb angle was significantly higher than that before operation (P < 0.001), and Δ Cobb angle was 7.4 ± 2.5˚, and all patients achieved bony fusion.ConclusionsEndoscopy-assisted ACDF, which combined the uniaxial spinal endoscopy with traditional ACDF, achieved satisfactory short-term clinical efficacy and safety in the treatment of CSM.